2004
DOI: 10.1097/01.mat.0000136505.27884.f8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Left Ventricular Assist Device Support and Outflow Graft Location Upon Aortic Blood Flow

Abstract: Although continuous flow (CFVAD) and pulsatile (PVAD) ventricular assist devices (VADs) are being clinically used, their effects upon aortic blood flow as a measure of overall blood distribution remain unclear. The objective of this study was to compare the effects of CFVAD and PVAD support for ascending (AscA) and descending (DA) aorta outflow cannulation upon mean aortic blood flow and waveform morphology. Six experiments were conducted in a normal, acute calf model, in which an inflow cannula was implanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…In the counterpulsation mode for the displacement pump (case 4) and in the reciprocating-valve pump (case 6), the left ventricle is more adequately unloaded. These coincide with corresponding results in similar research in Drakos et al's (2005) in vivo study on 18 domestic pigs, and Koenig et al's (2004) in vitro study in an adult mock circulation loop. According to previous researches, pulsatile flow has an important effect on the circulation physiology: it promotes perfusion in the kidney and liver, and promotes microcirculation at the cell level which is quite important in early treatment of acute heart failure (Sezai et al, 1999;Ü ndar, 2004).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the counterpulsation mode for the displacement pump (case 4) and in the reciprocating-valve pump (case 6), the left ventricle is more adequately unloaded. These coincide with corresponding results in similar research in Drakos et al's (2005) in vivo study on 18 domestic pigs, and Koenig et al's (2004) in vitro study in an adult mock circulation loop. According to previous researches, pulsatile flow has an important effect on the circulation physiology: it promotes perfusion in the kidney and liver, and promotes microcirculation at the cell level which is quite important in early treatment of acute heart failure (Sezai et al, 1999;Ü ndar, 2004).…”
Section: Discussionsupporting
confidence: 94%
“…It was concluded that the pulsatility associated with the intra-aortic balloon provides additional circulatory benefit with respect to the centrifugal pump alone. Litwak et al (2004) examined the effect of constant flow and pulsatile flow VAD support and outflow graft location on aortic flow in an acute calf model. Litwak et al (2005) and Koenig et al (2004) conducted similar research in an adult mock circulation test rig.…”
Section: Introductionmentioning
confidence: 99%
“…The descending aortic anastomosis also preserves the sternum for subsequent cardiac transplantation or other cardiac procedures that require a median sternotomy. So far, however, controversial results from some animal and in vitro studies have precluded wide use of this method, even for primary LVAD implantations [3,14,15]. Kar and colleagues [14] reported that LVADs implanted with an outflow-graft anastomosis to the descending aorta have potential drawbacks such as aortic valve fusion and aortic-root flow stagnation that may alter myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…All of these variables combine to result in a unique LVAD type–dependent normal flow-velocity pattern across the outflow cannula. 17,18 Outflow cannula malfunction adds yet another layer of complexity to the flow patterns of LVAD outflow cannulas. Accurate knowledge of the normal flow properties of a particular LVAD is therefore of particular importance because variations may indicate LVAD malfunction.…”
Section: Discussionmentioning
confidence: 99%